Argentine cinema : from noir to neo-noir - George, David Sanderson; Meneses, Gizella (Lexington Books, 2018)
This book presents a history of the development of film noir and neo-noir in Argentina, as well as a technical, aesthetic, and socio-historical analysis of recent Argentine neo-noir films. It also considers the question of neo-noir inscription of classic Hollywood noirs.